Essential Professional Skills for State Enterprise Accountants in the 21th Century: A Case Study of Provincial Electricity Authority, Area 1 (Central Region) - Aramrattanapan, Nujaree (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This paper aimed to explore required skills for accountants in the state enterprise based on International Education Standards (IES). The research sample was 21government officers, consisting of chief executive officers, middle managers, and staff members in the Provincial Electricity Authority, Area 1 (Central Region). The study employed the qualitative research approach. The data were collected by using in-depth interviews and then analyzed by the theme analysis approach by distinguishing the collected data on the basis of Initial Professional Development (Professional Skills), 3rd Issue, International Education Standard or IES3. The research findings revealed that 1) the current professional skills of accountants in the Provincial Electricity Authority consisted of intellectual, interpersonal, communication, self-management, and organizational management skills. 2) Essential professional skills required of accountants at State Enterprise in the twenty-first century were assessing data, achieving proficiency in assigned tasks, utilizing tools and technology, working as part of a team, recognizing cultural and language differences, being open-minded in accepting new opportunities, and managing people. 3) It was essential for supervisors to have interpersonal and communication skills. It was essential for staff members to have intellectual skills. Professional skills are a necessary part of organizational achievement. Executives should make improving the professional skills of its staff members a priority. In addition, professional accounting programs in educational institutions should take into account the enhancement of professional skills in four aspects: intellectual skills, interpersonal relationships and communication skills, self-management skills, and skills of organizational management. Article history : Received 30 April 2019 Revised 1 June 2019 Accepted 5 June 2019 SIMILARITY INDEX = 0.00 %